Economic Cost and Its Factors for COVID-19 vaccination among Adults in India: A Community Based Study - Kumar, Sunil; Hulugappa, Lakshmi; J, Srividya; S, Manjula; M M, Madhura (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Government of India introduced COVID-19 vaccination in January 2021. COVID-19 vaccination tends to increase the herd immunity in the community. There are limited studies on outof- pocket expenditure (OOPE) in COVID- 19 vaccination in India. Objective: The present study aims to estimate the OOPE for availing the COVID-19 vaccines and find the factors associated with OOPE. Methods: A community based cross- sectional study was conducted during September 2021- February 2022in urban poor locality, Bengaluru, India. A pre-tested validated semi-structured questionnaire was used to assess the direct and indirect costs for administration of COVID-19 vaccine in 438 participants above 18 years using probability proportional to population size by interview method. Data was analysed using descriptive statistics. Results: The total direct cost was $214.03USD, indirect cost was $4828.93USD for COVID-19 vaccination. Factors associated with higher OOPE was type of vaccine (OR=2.141, 95% CI=1.07-4.24) occupation of participant (OR=2.043, 95% CI= 1.37-3.03), reported stress following vaccination (OR=1.72, 95% CI=1.098- 2.703), adverse event within 48hrs (OR=2.125, 95% CI= 1.248-3.62), received any medication for adverse event (OR= 1.721, 95% CI= 1.022-2.84). Conclusion: The majority of the people utilized the government facility for vaccination. Factors associated with higher OOPE were: 2 times with type of vaccine, occupation of the study subject and adverse events within 48hrs. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 264-267